Canadian Pediatric Neuro-Oncology Standards of Practice - Bennett, Julie; Erker, Craig; Lafay-Cousin, Lucie; Ramaswamy, Vijay; Hukin, Juliette; Vanan, Magimairajan I.; Cheng, Sylvia; Coltin, Hallie; Fonseca, Adriana; Johnston, Donna; Lo, Andrea; Zelcer, Shayna; et al. (Frontiers in Oncology, 2020)
Primary CNS tumors are the leading cause of cancer-related death in pediatrics. It is essential to understand treatment trends to interpret national survival data. In Canada, children with CNS tumors are treated at one of 16 tertiary care centers. We surveyed pediatric neuro-oncologists to create a national standard of practice to be used in the absence of a clinical trial for seven of the most prevalent brain tumors in children. This allowed description of practice across the country, along with a consensus. This had a multitude of benefits, including understanding practice patterns, allowing for a basis to compare in future research and informing Health Canada of the current management of patients. This also allows all children in Canada to receive equivalent care, regardless of location.